2008
DOI: 10.1111/j.1469-8137.2008.02572.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination and infectivity of ectomycorrhizal fungal spores in relation to their ecological traits during primary succession

Abstract: Summary• The spores of ectomycorrhizal fungi (EMF) play critical roles in the population and community development of EMF. Here, the germination and infectivity of EMF spores are examined with reference to the ecological traits of the EMF species.• Spores were collected from 12 EMF species, whose successional patterns have been studied in the volcanic desert on Mount Fuji, Japan. Spore germination experiments were conducted with host plants (Salix reinii), with nonhost plants (Polygonum cuspidatum), and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 48 publications
7
53
0
Order By: Relevance
“…Population genetic studies have suggested that latestage EM fungi frequently reproduce via spores (Redecker et al 2001;Carriconde et al 2008), although these spores may be short-lived (Ishida et al 2008) or require specific conditions to germinate, such as the presence of microorganisms (Ali and Jackson 1989), mycelia of the same species (Fries 1987;Miller et al 1993), or older roots (Theodorou and Bowen 1987). Interspecific competition among fungal species (Kennedy and Bruns 2005) may also limit our ability to detect existing fungal spores.…”
Section: Discussionmentioning
confidence: 97%
“…Population genetic studies have suggested that latestage EM fungi frequently reproduce via spores (Redecker et al 2001;Carriconde et al 2008), although these spores may be short-lived (Ishida et al 2008) or require specific conditions to germinate, such as the presence of microorganisms (Ali and Jackson 1989), mycelia of the same species (Fries 1987;Miller et al 1993), or older roots (Theodorou and Bowen 1987). Interspecific competition among fungal species (Kennedy and Bruns 2005) may also limit our ability to detect existing fungal spores.…”
Section: Discussionmentioning
confidence: 97%
“…The ectomycorrhizal mushroom Tricholoma matsutake from southwestern China also showed limited (though statistically significant) genetic differentiation. The limited genetic differentiation between geographic populations in R. virescens could be due to several factors including natural long-distance dispersal of basidiospores [33] and human-aided dispersal through mushroom trading that could mix spores from distant populations. Unlike in the matsutake mushroom where fruiting bodies just before their caps open command significantly higher prices than those with open caps, there is relatively limited price difference between immature and mature Qingtoujun.…”
Section: Discussionmentioning
confidence: 99%
“…These are common pioneer fungi, with broad host ranges, high germination rates and the ability to quickly form ECM [71][73]. These two fungi therefore appear to be important components of the alpine ECMF spore bank, able to efficiently colonize the roots of establishing plants.…”
Section: Discussionmentioning
confidence: 99%